Reactive Amphiphilic Conjugated Polymers for Inhibiting Amyloid β Assembly. Issue 18 (26th March 2019) - Sun, Han; Liu, Jing; Li, Shengliang; Zhou, Lingyun; Wang, Jianwu; Liu, Libing; Lv, Fengting; Gu, Qi; Hu, Baoyang; Ma, Yuguo; Wang, Shu
Abstract: Protein misfolding and aberrant aggregations are associated with multiple prevalent and intractable diseases. Inhibition of amyloid assembly is a promising strategy for the treatment of amyloidosis. Reported here is the design and synthesis of a reactive conjugated polymer, a poly( p ‐phenylene vinylene) derivative, functionalized with p ‐nitrophenyl esters (PPV‐NP) and it inhibits the assembly of amyloid proteins, degrades preformed fibrils, and reduces the cytotoxicity of amyloid aggregations in living cells. PPV‐NP is attached to the proteins through hydrophobic interactions and irreversible covalent linkage. PPV‐NP also exhibited the capacity to eliminate Aβ plaques in brain slices in ex vivo assays. This work represents an innovative attempt to inhibit protein pathogenic aggregates, and may offer insights into the development of therapeutic strategies for amyloidosis. Abstract : Disassembly : A poly( p ‐phenylene vinylene) derivative functionalized with p ‐nitrophenyl esters (PPV‐NP) inhibits the assembly of amyloid proteins, degrades preformed fibrils, and reduces the cytotoxicity of amyloid aggregations in living cells. PPV‐NP is attached to the proteins through hydrophobic interactions and irreversible covalent linkages. This innovative approach offers new insights into the development of therapeutic strategies for amyloidosis.